Antioxidant and anticancer activities from aerial parts of Acalypha indica Linn. - Sanseera,D. (Chiang Mai University, 2015)
Extracts of Acalypha indica Linn. (aerial parts) were investigated for antioxidant activity, anticancer activity, and cytotoxicity. The extracts showed a non-cytotoxic response against Vero cells (African green monkey kidney). The anticancer activity of the extracts was tested using the Resazurin Microplate Assay (REMA). The methanol extract showed anticancer activity against NCIH187-Small Cell Lung Cancer with an IC50 of 25.00 μgmL-1. In addition, the hexane, chloroform, and methanol extracts also showed significant antioxidant activities with an IC50 of 6.19, 5.70, and 7.79 mg/mL, respectively, by means of the DPPH radical scavenging assay. The hexane, chloroform, and methanol extracts also showed significant antioxidant activities with an IC50 of 6.13, 6.31, and 6.37 mg/mL, respectively, by means of the ABTS radical scavenging assay. Isolation and purification of the methanolic extract of the aerial part produced substantial amounts of L-quebrachitol, which was characterized by 1D and 2D NMR experiments and the MS data.